PENINGKATAN APRESIASI SASTRA SISWA SLTP DENGAN PENDEKATAN RESEPSI SASTRA - Wiyatmi, Wiyatmi (Cakrawala Pendidikan, 2002)
This article is about a study conducted to improve students' attitude towards literature teaching and also to improve their appreciation of literature. The study was conducted on students in Class C of the second grade of the Yogyakarta Ninth Junior High School in the 2000/2001 academic year. It was conducted in two cycles, each cycle consisting of four steps, namely, planning, implementing treatment, monitoring and observing, and analyzing and reflecting. Data were collected by means ofobservations, field notes, tests, questionnaires onÂ  appreciation of literature, interviews, and tasks. The results of the study show that (1) the application of a literature teaching model that is appreciative and receptive and with practice in literature analysis could develop students' attitude towards literature teaching and (2) the application of such a model could develop students' appreciation of literature.